Studying the European consumer behavior and motivations towards tourism service in the condition of globalization - Zhurylo, Victoria (Technology audit and production reserves, 2017)
Features of a modern stage of the European tourist market development are considered and internal and external factors influencing formation of market behavior of consumers are analyzed. Development of the international tourism market largely depends on economic integration and globalization processes, improving the welfare of the population, expanding cultural ties and strengthening social interaction, demographic shifts, and socio-political stability in Europe. Under the influence of globalization and sociocultural shifts, changes in consumer preferences, transformations in the system of their motivation and market behavior significantly complicate the activities of travel companies, make them constantly monitor changes in consumer demand and find effective mechanisms for influencing market development. Analysis makes it possible to systematize the factors influencing the market behavior of consumers in the tourism industry, determine the determinants that are most influential in the process of making a consumer decision by the consumer. Based on the results of marketing research conducted in the UK tourism market, key factors of actualization and influence on consumer behavior are identified, the main reasons for acquiring tours, the directions of transformations of consumer behavior under the influence of globalization are revealed, and the hierarchy of consumer motives is compiled. Research results show that at the present stage of the functioning of the UK tourism market, the consumer is more inclined to individualize in making a purchasing decision, strives to satisfy hedonistic needs, gain new experience, develop personality and spiritual growth by studying other cultures, lifestyles and traditions. It is determined that the behavioral model of consumers illustrates the high resistance to the formation of global values and assimilation of cultures, personifies the preservation of behavioral identity and the stability of motivational elements. Understanding the market behavior of consumers under the influence of globalization in a cross-cultural context is very important from the point of view of the timely identification of transformations in behavioral consumption patterns and the development of effective marketing strategies for different segments of consumers in international markets.